THE INSTITUTIONAL FOUNDATIONS OF DISTANCE LEARNING IN HIGHER EDUCATION (Journal of Information Technologies in Education (ITE), 2010)
The results of pilot projects aimed at implementation of distance learning (e-learning) technologies in higher education on the example of the Lviv Academy of Commercial (LAC) are considered. They are based on information and communication technologies. The paths of institutional support for distance education technology, providing including reducing the uncertainty in the behavior of teachers in the development and implementation of distance learning courses, regulating their activities in some way are proposed.
Keywords: e-learning; institutional support for distance learning technologies; distance learning courses